Diagnosis of penicillin allergy revisited: the value of case history, skin testing, specific IgE and prolonged challenge - Hjortlund, J.; Mortz, C. G.; Skov, P. S.; Bindslev‐Jensen, C. (Allergy (Copenhagen), 2013)
Background Skin testing in duplicate, correlation between case history of immediate and nonimmediate reactions and challenge outcome and prolonged oral treatment with penicillin in the diagnostic evaluation of allergic reactions to β‐lactam antibiotics, mimicking real‐life situations, have only been addressed in few studies. Methods A total of 342 patients suspected of having β‐lactam allergy were investigated according to the European Network for Drug Allergy (ENDA) guidelines and patients found to be negative in the ENDA program were supplemented with a 7‐day oral treatment with penicillin. Skin testing with penicillins was performed in duplicate. Patients with case histories of reactions to other β‐lactams were also subsequently challenged with the culprit drug. Results Nineteen patients were IgE‐sensitized to penicillin. Then, intracutaneous tests (ICTs) were performed, in which 35 patients tested positive for allergy, 21 with delayed and 14 with immediate reactions. Only three patients tested positive for the major (PPL) and/or minor (MDM) penicillin determinants, all being positive for penicillin G in ICT. The remaining 291 patients were challenged with penicillin: 10 tested positive in single‐dose challenge and 23 tested positive in the 7‐day challenge. A total of 17 of 78 patients with a negative penicillin challenge tested positive during challenges with other β‐lactams. We found no correlation between case histories of immediate and nonimmediate reactions and reaction time during challenge. Conclusion The data suggest that case history is often insufficient to discriminate between immediate reactors and nonimmediate reactors. A 7‐day challenge with the culprit β‐lactam may yield more positive reactions than the accepted one‐ or 2‐day challenge. Interpretation of skin testing should be made with caution.